Bringing the information to the user through Library 2.0 / Al Bakri Mohammad and Siti Nuur-Ila Mat Kamal - Mohammad, Al Bakri; Mat Kamal, Siti Nuur-Ila (2011)
This paper defines "Library 2.0 as "user-centered change ". It is a model for library service that encourages purposeful change, inviting user participation in the creation of both the physical and the virtual services they want, supported by consistently evaluating services. It also attempts to reach new users and better serve current ones through improved customer-driven offerings. Library 2.0 or (L2) which is now more commonly addressed as - aims to take the information to the people by bringing the library service to the internet and getting the users more involved by encouraging feedback and participation. This paper seeks to present an overview of Library 2.0.